Analisis Spasial Tingkat Kerentanan Bencana Banjir Rob di Kabupaten Buton Tengah - Febriyanti Febriyanti; La Ode Muhammad Iradat Salihin; Fitra Saleh; Ahmad Hidayat (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2023)
Tidal flood is one of the disaster threats in Central Buton Regency. The phenomenon of tidal flood is caused by rising sea levels which have an impact on coastal and beach areas. At disaster mitigation, this research aims to; (1) Determine tidal flood hazard; (2) Determine tidal flood vulnerability. The tidal flood hazard parameters include: altitude, slope, aspect, distance from the sea, distance from the river, land use, rainfall, drainage density and soil type. Tidal flood vulnerability is analyzed based on physical vulnerability parameters including parameters of houses, public facilities and critical facilities. The data in this study were analyzed using scoring, weighting and overlay methods. The results of this study are: (1) The hazard level of tidal floods high class covering  292,30 acre (0.38%) in Gu, Lakudo, Mawasangka, Mawasangka Tengah, Mawasangka Timur and Sangia Wambulu, medium class covering 2.315,07 acre (3,02%), low class covering 8.131,16 acre (10,62%) and safe area of 65.823,92 acre (85.97%); (2)Areas that have high physical vulnerability, namely the coastal areas of Gu, Lakudo, Mawasangka, Mawasangka Timur, Sangia Wambulu.